(untitled) (Journal of the Bangladesh Agricultural University, 2019)
The Rht-B1 locus on the short arm of chromosome 4B has multiple alleles that give phenotypic expressions ranging from semi-dwarfism to extreme dwarfism. Allelic variation at Rht-B1 locus was also found in semi-dwarf Triticum polonicum L. cv. IC12196. The semi-dwarf allele from IC12196 could be an alternative source of reduced height gene. The experimental lines derived from the cross between Triticum aestivum L. cv. Novosibirskaya 67 (N67) and IC12196 were analyzed concerning the introgression of semi-dwarf allele from IC12196. The aim of the present study was to assess the selection for the semi-dwarfism and recombination around the locus of semi-dwarf gene using microsatellite markers on the short arm of chromosome 4B. The Rht-IC12196 allele was allelic to Rht-B1b allele, and microsatellite markers indicated that the Rht-IC12196 allele was linked with the markers, Xbarc1045 and Xgwm113 on the short arm of chromosome 4B. Out of 112 hexaploid introgression lines, 29 lines were semi-dwarf. The Xgwm113 and Xhbg226 markers flanking the Rht-B1 locus were replaced by N67 allele in the majority of introgression lines. Although it did not intend, the region around the Rht-B1 locus was highly selectable, but on short arms of chromosome 4B, Rht-IC12196 gene near the locus Xgwm113 explained a large part of the phenotypic variation originated from N67-allele and non-parental allele in tall accessions. The Rht-B1a allele was favorable in the consequence of bulk population breeding and the frequency of Rht-B1a allele was 73% in the hexaploid introgression lines. J. Bangladesh Agril. Univ. 17(2): 148–152, June 2019